ANALISIS PERENACANAAN ANGGARAN BERBASIS KINERJA DAN PELAKSANAAN ANGGRANA BERBASIS KINERJA DAN EVALUASI PELAPORAN TERHADAP AKUNTABILITAS KINERJA (STUDI KASUS PADA BADAN KARANTINA PERTANIAN JAKARTA) - Ferniyanti, Ningrum; Suratno, S; Supriyadi, Edy (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2019)
The aims of this study are to determine and empirically prove the effect of performance-based budget planning on performance accountability, the effect of implementation of clinic-based budgeting on performance accountability, and the effect of budget evaluation on performance accountability. Based on the results of research conducted, it can be concluded that there is no influence in budget planning on performance accountability because there are problems encountered so far, namely partial budget planning prepared by directorate staff who do not understand or are not budget planners so that budget revisions are made repeatedly causing budget execution to stall. The influence of the implementation of the budget on performance accountability. This proves that the better the implementation of the budget, the better performance accountability so that the output to be achieved will be achieved properly. The problems faced so far are the implementation of the budget that lacks understanding of the government's financial system, procurement procedures and mechanisms that are always changing, and government regulations that always change in the middle of the current budget year. The influence of the evaluation of reporting on performance accountability. This proves that the better the Reporting Evaluation, the better the accountability of performance so that the output to be achieved will be achieved properly.